UF/IFAS Nutrient Management Recommendation Series: Watermelon: SL522/SS735, 9/2024 - Hochmuth, Robert; Warren, Mark; Sanchez-Jones, Tatiana; Frey, Craig; Obreza, Thomas; Mylavarapu, Rao (EDIS, 2024)
Nutrient management recommendations for watermelon are described according to the standard UF/IFAS recommendation format of 1) a calibrated soil test result; 2) target soil pH; 3) the "4Rs" of fertilizer management: rate, timing, placement, and source; and 4) water management factors.